2020
DOI: 10.2147/cmar.s268565
|View full text |Cite
|
Sign up to set email alerts
|

<p>Diagnosis Value of Combined Detection of Serum SF, CEA and CRP in Non-Small Cell Lung Cancer</p>

Abstract: The aim of this study was to evaluate the clinical diagnostic value of combined detection of serum ferritin (SF), carcino-embryonic antigen (CEA) and C-reactive protein (CRP) in non-small cell lung cancer (NSCLC). Methods: The study included 70 patients with NSCLC, 50 patients with benign lung disease and 50 healthy subjects. The serum concentrations of SF, CEA and CRP were determined by ELISA. Results: The results showed that the serum levels of SF, CEA and CRP in the NSCLC group were significantly higher tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 20 publications
(16 reference statements)
2
10
0
Order By: Relevance
“…In our study, it was shown that smaller tumor diameter (<20 mm: HR: 2.437, 95% CI: 1.245-4.770, P=0.009) had a significant effect on stage I LUAD survival (AUC =0.592), which is consistent with a few previous studies (5,(43)(44)(45). Moreover, we found that postoperative CEA grouping (NN vs. NH, NN vs. HH; both P<0.001) had a considerable (31)(32)(33)(34)(35)(36). In these latter combination studies, a universal cutoff value or the reference value of the kit was used.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In our study, it was shown that smaller tumor diameter (<20 mm: HR: 2.437, 95% CI: 1.245-4.770, P=0.009) had a significant effect on stage I LUAD survival (AUC =0.592), which is consistent with a few previous studies (5,(43)(44)(45). Moreover, we found that postoperative CEA grouping (NN vs. NH, NN vs. HH; both P<0.001) had a considerable (31)(32)(33)(34)(35)(36). In these latter combination studies, a universal cutoff value or the reference value of the kit was used.…”
Section: Discussionsupporting
confidence: 91%
“…The expression of CEA also increases in patients with lung cancer, especially those with LUAD, and has higher diagnostic value than do the other types (28)(29)(30). Most relevant current studies have focused on either the predictive effect of the preoperative serum CEA level on the prognosis of patients or on combining serum CEA with other markers for diagnosis (31)(32)(33)(34)(35)(36). These reports are only the results of a one-time preoperative CEA test.…”
Section: Introductionmentioning
confidence: 99%
“…For this study, we selected CRP, LBP, and CD14, which are related to IL-8 production. A recent study described that CRP could improve the early diagnostic sensitivity of NSCLC, 60 and CRP was also significantly changed in our study. LBP is produced by lung parenchyma, and Chalubinska-Fendler et al have proposed that LBP may be a marker for evaluating radiotoxicity in NSCLC patients.…”
Section: Discussionmentioning
confidence: 57%
“…At present, CEA is more commonly applied to the diagnosis of adenocarcinoma in non-small cell lung cancer, but its cut-off level varies greatly in different studies (14,15). In one Chinese study, the serum CEA level of non-small cell lung cancer cases was found to be significantly higher than that of benign lung tumor cases and healthy people (16), while in another, the level in a lung adenocarcinoma group was significantly higher than that of a lung SCC group and small cell lung cancer group (17). While results such as those mentioned above show that CEA is of great significance for the clinical diagnosis of lung cancer, its role in early diagnosis is less convincing as it has poor specificity and its level of increase in the early stage of lung cancer is not obvious.…”
Section: Discussionmentioning
confidence: 98%